Substitution effects in intertemporal problems - Davide Dragone; Paolo Vanin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2020)
We consider a broad class of intertemporal economic problems and we characterize the short and long-run response of the demand for a good to a permanent increase in its market price. Depending on the interplay between self-productivity and time discounting, we show that dynamic substitution effects can generate price elasticities of opposite sign in the short and in the long run.
Keywords: D11; D91; I00; 330; Intertemporal substitution; Price elasticity; Tax reforms